Kontribusi Pendidikan Agama Islam terhadap Pengembangan Spiritualitas dan Mentalitas Peserta Didik - Etika Pujianti (Edukasia)
This research aims to analyze the contribution of Islamic Religious Education (PAI) to the development of students' spirituality and mentality, both in terms of strengthening faith and character formation. This study uses a method of reviewing the literature and analyzing various relevant reading sources, such as books, magazines, articles, and previous studies related to contribution of Islamic Religious Education (PAI) to the development of students' spirituality and mentality. The research results show that Islamic Religious Education (PAI) makes a significant contribution in building students' spiritual awareness through learning the values of faith, worship, and morals. In addition, the PAI program also helps develop a positive mentality such as a sense of responsibility, honesty, and discipline. However, this research also found several challenges, such as a lack of innovation in teaching methods and minimal student involvement in spiritual activities outside the classroom. Therefore, to optimize the contribution of PAI, it is necessary to utilize innovative teaching methods and integrate them with modern technology, as well as support from the family and community environment. Furthermore, PAI teachers must continue to improve their competencies to face the dynamics of the times and provide learning that is more relevant to the needs of students. Overall, Islamic Religious Education plays a fundamental role in shaping a generation that is not only academically intelligent but also possesses deep spiritual and mental strength. PAI serves as a foundation for shaping balanced, responsible individuals who are able to face life with integrity and maturity.